(3aJhM CQV QHjYI hOjGQ HcQ hGdLRjQI hGdYQGbs - (3eMeO Hf YeQ Hf hGbO GdSgej GdCSdej HGdhdGA, GdeOfj, CHh YHO Gddg, GdhGbOj,J (B207 (3g` s
(3ChdgG (B:s
(3aJhM GdLRjQI , bGd(B: (3MOKfG jhfS Hf YHOGdCYdi s
(3BNQgG (B:s
(3bGd GdhGbOj QMeg Gddg(B: (3hde jRd GdSja jYed ai GdQbGH hCTQb GdVhA fMh GdeTQb hdGM s
(3GfXQ HQbe (B358 (3JGQjNs
(3fSNI KGfjI hCdMb HGdYfhGf bhdg(B: (3ef aJhM GdTGes
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B95s
Keywords: (3GdJGQjNs